THE CORRELATION BETWEEN THE REFERENCE GROUP, ACCESSIBILITY AND FACILLITY COMPLETENESS, AND THE REQUEST FOR PREVENTIVE DENTAL HEALTH CARE SERVICES AT THE PUBLIC HEALTH CENTERS IN DENPASAR CITY IN 2011 - Ni Putu Suarniti (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
The utilization of Public Health Centre still have  been choosen for health care, included for dental health care. The study was aiemed at identifying attempt made to preventively take care of teeth at BPG of the Public Health Centers in Denpasar City is intended to improve the peoples’s tooth and mouth. However, the request for the attempt made to preventively take care of teeth is lower than the request for the attempt made to care teeth. This studied aims at identified the facility completeness, and the request for preventive tooth care services at the Public Health Centers in Denpasar City. This study was a non experimental one with cross sectional planning. 100 respondents, which were taken using proportional random sampling technique, were use as the samples. The data were analyzed using univariate and bivariate. The result of Spearman correlations test showed that there were three insignificant variables health services facilities was r=0.333** and p ≤0.05. The facilitu completeness dominanty correlated with preventive tooth health care services at the Public Health Centers in Denpasar City